2005
DOI: 10.1016/j.neuron.2004.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Theta Burst Stimulation of the Human Motor Cortex

Abstract: It has been 30 years since the discovery that repeated electrical stimulation of neural pathways can lead to long-term potentiation in hippocampal slices. With its relevance to processes such as learning and memory, the technique has produced a vast literature on mechanisms of synaptic plasticity in animal models. To date, the most promising method for transferring these methods to humans is repetitive transcranial magnetic stimulation (rTMS), a noninvasive method of stimulating neural pathways in the brain of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

81
2,754
15
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 3,412 publications
(2,866 citation statements)
references
References 35 publications
81
2,754
15
16
Order By: Relevance
“…Thus, TBS over sensory cortex has effects on SEPs that are parallel to its effects on MEPs when applied over M1 where cTBS suppresses MEPs and iTBS facilitates them (Huang et al, 2005). However, in contrast to the previous study, where opposite effects on the SEP were observed when cTBS was moved to M1, here we saw no effect on SEPs if iTBS was performed on M1.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Thus, TBS over sensory cortex has effects on SEPs that are parallel to its effects on MEPs when applied over M1 where cTBS suppresses MEPs and iTBS facilitates them (Huang et al, 2005). However, in contrast to the previous study, where opposite effects on the SEP were observed when cTBS was moved to M1, here we saw no effect on SEPs if iTBS was performed on M1.…”
Section: Discussioncontrasting
confidence: 93%
“…We did not evaluate whether M1 iTBS had any effect on MEPs because of concerns that this might interfere with SEP. However, since the same stimulus parameters produced clear effects on the SEP when applied over S1, it seems likely that stimulation over M1 would have produced the usual facilitation of MEPs reported by Huang et al (2005). Thus one explanation of these results is that motor cortex circuits responsible for modulating SEPs after cTBS over M1 are not affected by iTBS over M1.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Continuous theta burst stimulation (cTBS) was used to depress the function of the vermis region of the cerebellum. cTBS, when applied to the motor cortex as well as the cerebellum, has been shown to inhibit the output of neurons through what is believed to be a depletion of neurotransmitter (Huang et al., 2005; Koch et al., 2008; Popa, Russo, & Meunier, 2010). In the cerebellum, it is postulated that the depressive effects take place at the synapse between Purkinje cells and climbing fibers, parallel fibers or mossy fibers, inhibiting Purkinje output, and thus decreasing the inhibitory effects on the deep cerebellar nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…TMS was applied to the cerebellar vermis, located directly beneath the inion [located by palpating the base of the skull, (Hashimoto & Ohtsuka, 1995)] with the coil held tangentially to the scalp with the handle pointing upwards. Subjects received continuous theta burst stimulation (cTBS), a pattern of repetitive TMS (bursts of 3 pulses of 50 Hz stimulation, repeated at 5 Hz (every 200 ms), for a total of 600 stimuli over 40 seconds (Huang, Edwards, Rounis, Bhatia, & Rothwell, 2005). cTBS was administered at each subject's 100% AMT, as described above (Demirtas‐Tatlidede, Freitas, Pascual‐Leone, & Schmahmann, 2011).…”
Section: Methodsmentioning
confidence: 99%